Assessing the potential of diverse pastures for reducing nitrogen leaching - Graham, Scott L.; Pronger, Jack; Laubach, Johannes; Hunt, John E.; Rogers, Graeme N. D.; Carrick, Sam; Whitehead, David; McLeod, Malcolm; Mitchell, Grace; Mudge, Paul (Frontiers in Environmental Science, 2024)
Mitigation practices for nitrogen leaching losses from livestock agriculture are needed to protect freshwater quality and increase the efficiency of agricultural production. Within New Zealand, the most common pasture type is a two-species mix of perennial ryegrass (Lolium perenne) and white clover (Trifolium repens). Ecological theory suggests that increasing species and functional diversity improves ecosystem function, including nitrogen (N) retention. Use of more diverse pasture types, including a mix of pasture grasses, legumes and other forbs, particularly plantain (Plantago lanceolata), with functional traits, including winter activity, deep-rooting, N fixation, and biological inhibition of nitrification in the soil, is a potential mitigation practice that requires further verification with long-term field measurements. Here we utilize a network of large lysimeters to make field-based measurements of N leaching from 5-8 species diverse pasture, including plantain, under a range of soil, climate and management conditions, for comparison with losses from traditional ryegrass-clover pasture. Over three years of measurements, leaching from fully established diverse pasture was 2-80 kg N ha -1 y -1 . No differences were observed in dry matter production or N leaching of diverse pasture compared to ryegrass-clover lysimeters. Large losses, up to 120 kg N ha -1 , were observed during periods when pasture was not fully established, including cultivation and sowing of new pasture, depending on season. Timing of management activities could be optimized to minimize these losses. These data provide critical assessment of diverse pasture as a mitigation approach for reducing N losses. Further work on diverse pastures should include higher diversity mixes as well as consideration of animal mediated effects of diverse pasture diets on N inputs.